Periurban landscapes in mountain areas - Nathalie Bertrand; Sylvie Vanpeene-Bruhier (Revue de Géographie Alpine)
Changes in regional landscapes due to urban pressures raise questions regarding land use. They also give rise to economic, social and environmental issues related to urban sprawl, increases in daily commuting, and land consumption. These changes and dysfunctions are ultimately underpinned by the question of sustainable regional development. Mountain regions such as the Alps, with their various outstanding biotopes in a restricted space, are particularly vulnerable.